Cinematography for female objectification: Analysis of item songs of Pakistani movies - Aksar, Iffat; Jiang, Xuege; Gong, Jiankun (Frontiers in Communication, 2022)
The transition in Pakistani cinema and terming it as a rival to cinema is heavily dependent on the bowing technique of item songs, which deliberately fuels the negative representation of women. The qualitative analysis of item songs underlined the representation of women and shed light on aspects such as how the objectification of women in item songs is done in a patriarchal society and what values are assigned on the basis of gender. The analysis of item songs revealed that women are sexually objectified and the use of clothing, jewellery, makeup, body movements, and gestures are filmed to enhance the female body. As a result, the majority of the songs feature women as objects of sensation and enjoyment. On the other hand, though the notion of women’s empowerment has been raised all over the world, cinema still presents them in a submissive way and defines their role to please men. The dominance of the male is projected, and the close body angles of women’s body gestures and nude body parts show their vulnerability. The female’s visualisation reflects that she is presented tactfully to the audience, and her vulnerable role is reinforced. Keywords: Item songs, Male Gaze, Patriarchal Cinema, Objectification, Cinematography